2021
DOI: 10.1002/prot.26039
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐induced transition in conformations of vicinal cysteine disulfides in proteins

Abstract: Vicinal cysteine disulfides are thought to be associated with specific conformations of cysteine disulfides due to the restricted rotation of single bonds in an eightmembered cyclic disulfide loop. Conformations of vicinal cysteine disulfides are analyzed using χ 1 , χ 2 , χ 3 , χ 2 ', χ 1 ' torsion angles in the crystal structures of proteins retrieved from Protein Data Bank (PDB). 85% of vicinal disulfides have (+, −)LHStaple conformation with trans configuration of the peptide bond and 9% have (−, −) RHStap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The higher values correspond to the two reactions that lead to a vicinal disulfide bond between the adjacent cysteines S78 and S79. Vicinal disulfides constitute the smallest possible intramolecular disulfide loops, which experience a high steric strain due to their small ring size. , Thus, a higher barrier has to be overcome to form the bond S78–S79, which also lies higher in energy than the other two disulfide bonds, S36–S78 and S79–S36. All other investigated thiol–disulfide exchange reactions have barriers around 9 kcal/mol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The higher values correspond to the two reactions that lead to a vicinal disulfide bond between the adjacent cysteines S78 and S79. Vicinal disulfides constitute the smallest possible intramolecular disulfide loops, which experience a high steric strain due to their small ring size. , Thus, a higher barrier has to be overcome to form the bond S78–S79, which also lies higher in energy than the other two disulfide bonds, S36–S78 and S79–S36. All other investigated thiol–disulfide exchange reactions have barriers around 9 kcal/mol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…3(c) box). 6,[17][18][19] We have found that the amide in the fused bicyclic pyrrolidine ring (5), that is, a bicyclic proline skeleton bearing a bridgehead substituent, forms exclusively a trans-amide structure, despite being a tertiary amide (Fig. 1(d)).…”
mentioning
confidence: 94%
“…However, the vicinal disulfide ring conformations in proteins often undergo conformational change in response to nearby ligand binding, and this can generate rare and highly strained conformations such as trans-(+, -)AntiRHHook, which has (χ 1 , χ 2 , χ 3 , χ 2' , χ 1' ) = (+,-,+,+,-) (see Figure 3c box). 6,17,18,19 We have found that the amide in the fused bicyclic pyrrolidine ring (5), that is, a bicyclic proline skeleton bearing a bridgehead substituent, takes exclusively trans-amide structure, despite being a tertiary amide (Figure 1d). 20,21 These results inspired us to consider molecules with a similar bicyclic skeleton, in which the amide isomerism might be switched from exclusively trans to exclusively cis and vice versa, concomitantly with disulfide ring formation and cleavage, respectively.…”
mentioning
confidence: 97%
See 2 more Smart Citations